Dialogue, deliberation and human rights - Young, A (Cambridge University Press, 2018)
The chapter examines the connection between theories of deliberation and democratic dialogue. It argues that adding a component of deliberation will not, in and of itself, resolve definitional and stability issues which arise in accounts of democratic dialogue. However, it argues that deliberation is a goal that may be fostered by democratic dialogue and that an assessment of deliberation may help to choose between different legal mechanisms designed to facilitate democratic dialogue.